Characterization of the channel properties of a neuronal acetylcholine receptor reconstituted into planar lipid bilayers (The Rockefeller University Press, 1987)
An alpha-toxin-binding membrane protein, isolated from the head and thoracic ganglia of the locus (Locusta migratoria), was reconstituted into planar lipid bilayers. Cholinergic agonists such as acetylcholine, carbamylcholine, and suberyldicholine induced fluctuations of single channels, which suggests that the protein represents a functional cholinergic receptor channel. The antagonist d-tubocurarine blocked the activation of the channels, whereas hexamethonium had only a weak effect; similar properties have been described for nicotinic insect receptors in situ. The channel was selectively permeable to monovalent cations but was impermeable to anions. The conductance of the channel (75 pS in 100 mM NaCl) was independent of the type of agonist used to activate the receptor. Kinetic analysis of the channel gating revealed that, at high agonist concentrations (50 microM carbamylcholine), more than one closed state exists and that multiple gating events, bursting as well as fast flickering, appeared. At very high agonist concentrations (500 microM carbamylcholine), desensitization was observed. Channel kinetics were dependent on the transmembrane potential. Comparing the conductance, the kinetics, and the pharmacology of nicotinic acetylcholine receptor from insect ganglia and fish electroplax reconstituted into bilayers revealed obvious similarities but also significant differences.